Street Art & Graffiti in Belgrade: Ecological Potentials? - Tunic, Srdan (SAUC - Street Art and Urban Creativity (repository), 2020)
Since the emergence of the global contemporary graffiti and street art, urban spaces have become filled with a variety of techniques and art pieces, whether as a beautification method, commemorative and community art, or even activism. Ecology has also been a small part of this, with growing concern over our environment’s health (as well as our own), disappearing living species and habitats, and trying to imagine a better, less destructive humankind (see: Arrieta, 2014). But, how can this art - based mostly on aerosol spray cans and thus not very eco-friendly - in urban spaces contribute to ecological awareness? Do nature, animal and plant motifs pave a way towards understanding the environment, or simply serve as aesthetic statements? This paper will examine these questions with the example of Belgrade, Serbia, and several local (but also global) practices. This text is based on ongoing research as part of Street Art Walks Belgrade project (STAW BLGRD) and interviews with a group of artists.